1998
DOI: 10.1053/euhj.1997.0732
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial damage during percutaneous transluminal coronary angioplasty as evidenced by troponin T measurements

Abstract: AimThe present study was undertaken to assess the effect of balloon inflation during percutaneous transluminal coronary angioplasty on markers of myocardial damage. Methods and resultsSeventy-five patients undergoing elective percutaneous transluminal coronary angioplasty were evaluated with serum creatine kinase MB and cardiospecific troponin T before and 1 and 4 days after the procedure. On day 1, 28% of the patients had increased cardiospecific troponin T values and 18% had increased creatine kinase MB valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 17 publications
2
29
0
1
Order By: Relevance
“…[16][17][18][19] The incidence of TnT release exceeding the cut-off point in the control group of our study was 42%, which is similar to that (44%) reported by Karim, et al 16) but higher than those (13% and 8.9%, respectively) reported by Shyu, et al 17) and Ohnishi, et al 19) The difference in the incidence of TnT release may be due to the difference in the total balloon inflation time during angioplasty. 18) Intracoronary pressure-derived CFI has often been used for evaluating coronary collateral function during coronary angioplasty. 14) We have revealed that nicorandil-induced preconditioning during coronary angioplasty is independent of collateral recruitment using the same CFI.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…[16][17][18][19] The incidence of TnT release exceeding the cut-off point in the control group of our study was 42%, which is similar to that (44%) reported by Karim, et al 16) but higher than those (13% and 8.9%, respectively) reported by Shyu, et al 17) and Ohnishi, et al 19) The difference in the incidence of TnT release may be due to the difference in the total balloon inflation time during angioplasty. 18) Intracoronary pressure-derived CFI has often been used for evaluating coronary collateral function during coronary angioplasty. 14) We have revealed that nicorandil-induced preconditioning during coronary angioplasty is independent of collateral recruitment using the same CFI.…”
Section: Discussionsupporting
confidence: 84%
“…However, other similar studies followed TnT levels in patients undergoing elective coronary angioplasty for more than 24 hours. [16][17][18][19] The peak values of TnT elevation may have been seen after an 18-hour rest period in this study. The stenotic lesion was located in one of the three major coronary arteries, therefore, some potential differences in TnT release due to the lesion site were not considered.…”
Section: Vol 43 Nomentioning
confidence: 48%
See 1 more Smart Citation
“…25 Similar procedural injury to the heart has been extensively documented secondary to coronary interventions by measurements of elevations in troponin levels (so-called troponin "leak") and constitutes justification for the current stringent training standards for coronary intervention. 26,27 In addition to the technical risks of cerebrovascular procedures, there is also a risk of misdiagnosis if images are not interpreted correctly. This fact justifies formal and adequate cognitive training related to neurological and neurovascular anatomy, neurodiagnostic imaging, and neuro-pathophysiology.…”
Section: Risks Of Cervicocerebral Angiographic Procedures Risks Of Dmentioning
confidence: 99%
“…Studies have documented that elevation of postprocedural serum cardiac troponin is relatively common 1,2 and that markedly elevated levels of troponin after PCI are prognostically significant 3,4 ; however, uncertainties remain about the mechanisms and functional significance of small troponin releases after PCI and the direct relationship between procedure-related troponin rise and the volume of myocardial tissue loss. Despite these concerns, current European Society of Cardiology/American College of Cardiology guidelines recognize elevation of cardiac troponin within 24 hours of a PCI procedure in the definition of myocardial infarction.…”
mentioning
confidence: 99%